Context-relevant strategic decision-making by leaders under crisis conditions - Toefy, Rashid (Graduate School of Business (GSB), 2026)
In recent years, the field of crisis leadership has garnered increased scholarly attention due to the unparalleled challenges faced by leaders globally. The study investigated how leaders navigated crises such as natural disasters, pandemics, and geopolitical conflicts, and how their diverse contexts influenced their decision-making amidst uncertainty and change. The primary research question explored was: How do different contexts influence the strategic decision-making behaviours of leaders under crises conditions? The participants in this study, 16 female and 16 male senior leaders from 18 different countries around the world, were either the CEO or the executive head of a division within an organisation, both public and private sector, from a range of industries, who had led organisations during a crisis. Using an inductive, qualitative research approach, with data collected using semi-structures interviews, the research explored the lived experiences and personal journeys of the research participants, using Rational Choice Theory and Stakeholder Theory as its theoretical framework. The study aimed to expand upon four primary strands of existing literature: the nature of leadership in times of crisis; the strategic decision-making process and its context-dependency; the critical leadership behaviours that form the foundation of strategic decisions during crises and an analysis of the role of gender and diversity when leaders are faced with crisis conditions. The research transcended any single crisis event, instead examining the broader impact of various contexts on the strategic decision-making of leaders and did not restrict itself to the challenges faced by a single organisation, but rather explored larger-scale events that affected entire cities, countries, regions, or had global ramifications. This study contributes to the extant literature by exploring the nuances of leadership in crisis conditions, the importance of context, and the need for inclusive leadership, emphasising how times of crisis necessitate a balance of swift intuitive action and evidence-based decision-making, incorporating diverse perspectives. The thesis proposes a Crisis Decision-Making Framework, recognising the collective strength of sensemaking, intuitive decision-making, and context diversity in making robust strategic decisions in crisis conditions